Ser educador quilombola é nos encontrar uns nos outros: uma etnografia sobre educação quilombola antirracista baseada na ciência do quilombo de extrema - Rocha, Márcia Sacramento (2023)
The present ethnography addresses the mechanisms we use to fight for our existences through the antiracist quilombola education in Extrema. We present the battles against racism in the life of my people who have been resisting by playing, wandering in the quilombo based on our ancestral disobedience and quilombo stubbornness. Thus, we try to understand between the lines of racism that my quilombola people of Extrema have been living for years. What are the implications that all the racist violence has been causing in the lives of the quilombolas? What are the mechanisms that my people from Extrema have been using as essential tools to fight and confront racism on a daily basis? We also built a methodology from the inside, and in this way, we will dialogue from life and from the history of resistance of the Quilombolas of Extrema. Our general objective is to investigate and analyze in detail the teaching and learning practices in the Quilombo of Extrema, based on the knowledge of the Quilombolas and on our science, which remains alive despite the violence they have suffered.